The role of intervening hospital admissions on trajectories of disability in the last year of life: prospective cohort study of older people - Thomas M. Gill; Evelyne A. Gahbauer; L. Han; Heather Allore (2015)
Objective To evaluate the role of intervening hospital admissions on trajectories of disability in the last year of life. Design Prospective cohort study. Setting Greater New Haven, Connecticut, United States, from March 1998 to June 2013. Participants 552 decedents from a cohort of 754 community living people, aged 70 years or older, who were initially non-disabled in four essential activities of daily living: bathing, dressing, walking, and transferring. Main outcome measure Occurrence of admissions to hospital and severity of disability (range 0-4), ascertained during monthly interviews for more than 15 years. Results In the last year of life, six distinct trajectories of disability were identified, from least disabled to most disabled: 95 participants (17.2%) had no disability, 61 (11.1%) had catastrophic disability, 53 (9.6%) had accelerated disability, 61 (11.1%) had progressively mild disability, 127 (23.0%) had progressively severe disability, and 155 (28.1%) had persistently severe disability. 392 (71.0%) participants had at least one hospital admission and 248 (44.9%) had multiple hospital admissions. For each trajectory the course of disability closely tracked the monthly prevalence of hospital admission. In a set of multivariable models that included several potential confounders, hospital admission in a given month had a strong independent effect on the severity of disability, in both relative and absolute terms. The largest absolute effect was observed for catastrophic disability, with a mean increase in disability score of 1.9 (95% confidence interval 1.5 to 2.4) in the setting of a hospital admission, corresponding to a rate ratio (or relative effect) of 2.0 (95% confidence interval 1.5 to 2.7). Conclusions In the last year of life, acute hospital admissions play an important role in the disabling process. Knowledge about the course of disability before these intervening events may facilitate clinical decision making at the end of life. For older patients admitted to hospital with progressive or persistent levels of severe disability, representing more than half of the decedents, clinicians might consider a palliative care approach to facilitate discussions about advance care planning and to better deal with personal care needs.